Integration processes in modern sport science under transition - Lubysheva, L. I.; Mochenov, V. P. (Theory and Practice of Physical Culture, 2018)
The study analyzes modern trends in sport science and effects of the relevant socio-cultural processes on the research in the physical education and sports sector, with an emphasis on the theoretical and practical groundwork for the modern integration processes in the sport science and the key practical problems that need to be solved to secure further progress of the sport science. Presently the situation in the sport science is dictated by the transition to the breakthrough research technologies driven by interdisciplinary research projects facilitated by the close and effective cooperation in a variety of research disciplines coordinated and driven by an umbrella (integrative) research theory.